2015
DOI: 10.1002/app.42927
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the coupling agent and graphene oxide on the thermal and mechanical behavior of tea dust–polypropylene composites

Abstract: In this study, the effects of a coupling agent and additive on the physicomechanical (morphological, mechanical, thermal, and swelling) properties of tea dust (TD)–polypropylene (PP) composites were studied. TD–PP composites were prepared with untreated tea dust (UTD) and tetraethylsilane (TES)‐treated TD or silanated tea dust (STD) particles at ratios of 0:100, 10:90, 20:80, 30:70, and 40:60 w/w. Initially, TD particles were grafted by TES as a coupling agent, and these STD particles were then modified with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 65 publications
0
29
0
1
Order By: Relevance
“…This treatment eliminated low molecular weight species and hemicelluloses . In previous study, FTIR spectra revealed that surface treatment of TD particles can remove hemicelluloses, lignin type materials and which was confirmed from the absence of spectra (1370–1330 cm −1 of in‐plane CH bending of hemicelluloses and 1505–1520 cm −1 for lignin) in treated TD particles. These TD particles were denoted as “styrene treated TD” (STD) particles.…”
Section: Methodsmentioning
confidence: 57%
See 3 more Smart Citations
“…This treatment eliminated low molecular weight species and hemicelluloses . In previous study, FTIR spectra revealed that surface treatment of TD particles can remove hemicelluloses, lignin type materials and which was confirmed from the absence of spectra (1370–1330 cm −1 of in‐plane CH bending of hemicelluloses and 1505–1520 cm −1 for lignin) in treated TD particles. These TD particles were denoted as “styrene treated TD” (STD) particles.…”
Section: Methodsmentioning
confidence: 57%
“…Then PP composites were prepared by reinforcing the STD particles in matrix. Molecular mechanism and FTIR spectra of untreated and MA and tetra ethyl silane treated TD particles have been discussed . Surface treatment has been confirmed from XRD analysis.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, graphene is a basic building block of graphitic materials having all dimensionalities and used in the synthesis of a variety of composite blend films and polymer nanocomposites. However, graphene sheets have a high specific surface area, and tend to form irreversible agglomerates or even restack to form graphite through van der Waals interactions . So, many scientists have prepared hybrid nanostructures of GO with different organic and inorganic materials to overcome this problem of GO.…”
Section: Introductionmentioning
confidence: 99%